Predictive biomarkers for response of esophageal cancer to chemo(radio)therapy: A systematic review and meta-analysis. (December 2017) - Li, Yang; Huang, He-Cheng; Chen, Long-Qi; Xu, Li-Yan; Li, En-Min; Zhang, Jian-Jun
Abstract: Background: Esophageal cancer remains a major public health issue worldwide. In clinical practice, chemo(radio)therapy is an important approach to patients with esophageal cancer. Only the part of patients who respond to chemo(radio)therapy achieve better long-term outcome. In this case, predictive biomarkers for response of esophageal cancer patients treated with chemo(radio)therapy are of importance. Meta-analysis of P53 for predicting esophageal cancer response has been reported before and is not included in our study. We performed a systematic review and meta-analysis to summarize and evaluate the biomarkers for predicting response to chemo(radio)therapy. Method: PubMed, Web of Science and the Ovid databases were searched to identify eligible studies published in English before March 2017. The risk ratio (or relative risk, RR) was retrieved in articles regarding biomarkers for predicting response of esophageal cancer patients treated with neoadjuvant therapy or chemo(radio)therapy. Fixed and random effects models were used to undertake the meta-analysis as appropriate. Result: Forty-six articles reporting 56 biomarkers correlated with the response were finally included. Meta-analyses were carried out when there was more than one study related to the reported biomarker. Results indicated that low expression of (or IHC-negative) COX2, miR-200c, ERCC1 and TS was individually associated with prediction of response. The RR was 1.64 (n = 202, 95% CI 1.22–2.19, P < 0.001), 1.96 (n = 162, 95% CI 1.36–2.83, P < 0.001), 2.55 (n = 206, 95% CI 1.80–3.62, P < 0.001) and 1.69 (n = 144, 95% CI 1.10–2.61, P = 0.02), respectively. High expression of (or IHC-positive) CDC25B and p16 was individually related to prediction of response. The RR was 0.62 (n = 159, 95% CI 0.43–0.89, P = 0.01) and 0.62 (n = 142, 95% CI 0.43–0.91, P = 0.01), respectively. Conclusion: Low expression of (or IHC-negative) COX2, miR-200c, ERCC1 and TS, or high expression of (or IHC-positive) CDC25B and p16 are potential biomarkers for predicting the response of esophageal cancer patients treated with chemo(radio)therapy. Highlights: Low expression such as ERCC1, miR200C and TS can predict esophageal response. High expression CDC25B, p16 was a potential biomarker for predicting the response. Only patients who response to chemo(radio)therapy can achieve a beneficial outcome. Potential predictive biomarkers were summarized and evaluated. Both qualitative and quantitative method were used in evaluated these biomarkers.